Variación en los ingresos de la Farmacia Sanasana matriz San Cristóbal provincia de Galápagos. - Aldaz Cabrejo, Ginger Jasmin (2022)
The research was carried out at the Farmacéutica SanaSana, which is dedicated to the retail sale of pharmaceutical products in specialized establishments. The main purpose of SanaSana has been based on community service, being a pharmacy that is characterized by offering friendly and simple treatment. Its economic activity is the retail sale of specialized pharmaceutical products. The reason that leads to carrying out this case study is that there are various problems within the company, which will be detailed in the course of the investigation. The business model revolves around the pharmaceutical sector, with the marketing of medicines and non-medicines. The main purpose of SanaSana has been based on community service, being a pharmacy that is characterized by offering a friendly and simple treatment. Its priority is the client, which is why it is always at the forefront of the needs of its users. The methodology used is the descriptive method through bibliographical research that will allow explaining in a more detailed way the deficiencies that occur in the pharmacy, in addition techniques such as observation and interview will be used.